The Effect of Vitamin A on Testis Weight and Sexual Glands on Albino Male Mice Treated with Hexavalent Chromium (Baghdad Science Journal, 2014)
This study was conducted to determine the effect of vitamin A ( 10 mg/kg ) on avearage testis weight and sexual glands ( Prostate and Seminal Vesicle ) for albino male mice treated with Hexavalent chromium ( 1000 ppm ) .The current study 40 mice were divided into fife groups : 1st group treated with distilled water and considered an control group (C) / the 2nd group treated with sesame oil ( T1) / 3rd group was givin hexavalent chromium ( 1000 ppm ) (T2) / 4th group treated with vitamin A ( 10 mg / kg ) and exposed to hexavalent chromium ( 1000 ppm ) (T3) / 5th group treated with vitamin A ( 10 mg kg ) (T4) . The expermint lasted 35 day . the results showed a significant ( P ? 0.05 ) decrease in avearage testis weight and sexual glands ( Prostate and Seminal Vesicle ) as compared with control group . Results also showed a significant ( P ? 0.05 ) increase in avearage testis weight and sexual gland (Prostate and Seminal Vesicle ) in the group treated with vitamin A and exposed to hexavalent chromium in comparison with group that treated with hexavalent chromium . the last group that treated with vitamin A showed a best significant ( P ? 0.05 ) increase in all the parameters studied in comparison with group treated with sesame oil . In conclusion , vitamin A had positive effect on fertility of albino male mice through its effect at testis and sexual glands ( Prostate and Seminal Vesicle ) weights by improving the negative effect caused from exposing to hexavalent chromium .